2006
DOI: 10.1200/jco.2005.02.5577
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Neoadjuvant Chemotherapy and Radiation Therapy in the Management of High-Risk, High-Grade, Soft Tissue Sarcomas of the Extremities and Body Wall: Radiation Therapy Oncology Group Trial 9514

Abstract: This combined-modality treatment can be delivered successfully in a multi-institutional setting. Efficacy results are consistent with previous single-institution results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
184
3
8

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(212 citation statements)
references
References 25 publications
17
184
3
8
Order By: Relevance
“…Postoperative radiotherapy as an adjunct to surgical treatment is required for the patients with large and high grade tumors and with close or positive margins (Lindberg et al, 1981;Wouters et al, 2008;Burt et al, 2013). On the other hand preoperative radiotherapy, chemotherapy, or combined chemoradiotherapy can be applied to these patients in order to allow more conservative surgery with negative margins (Kraybill et al, 2010;Burt et al, 2013). Some authors recommended preoperative radiotherapy when close margins were anticipated in order to improve LC and DFS (Kachroo et al, 2012;Gronchi et al, 2013).…”
Section: Long-term Treatment Results In Soft Tissuementioning
confidence: 99%
“…Postoperative radiotherapy as an adjunct to surgical treatment is required for the patients with large and high grade tumors and with close or positive margins (Lindberg et al, 1981;Wouters et al, 2008;Burt et al, 2013). On the other hand preoperative radiotherapy, chemotherapy, or combined chemoradiotherapy can be applied to these patients in order to allow more conservative surgery with negative margins (Kraybill et al, 2010;Burt et al, 2013). Some authors recommended preoperative radiotherapy when close margins were anticipated in order to improve LC and DFS (Kachroo et al, 2012;Gronchi et al, 2013).…”
Section: Long-term Treatment Results In Soft Tissuementioning
confidence: 99%
“…26,28,35 Such a distinction encompasses, in addition to tumor necrosis, the presence of fibrosis and acellular matrix as elements of nonviable tumor, and cumulatively represents treatment effect. In routine practice, a pathologist would presumably consider the entire area occupied by necrotic cells, acellular matrix, and loose fibrous tissue in estimating the extent of ''necrosis.''…”
Section: Discussionmentioning
confidence: 99%
“…More recent efforts have explored the use of interdigitated radiotherapy with doxorubicin-containing chemotherapy regimens such as MAID (mesna, doxorubicin, ifosfamide, and dacarbazine). Favorable outcome with this schedule, though substantially greater short-term toxicities has been reported (Kraybill et al, 2010). We prefer to use doxorubicin, ifosfamide with mesna (AIM) rather than MAID regimen while there are several published data showing good results with high dose adriamycin and ifosfamide with G-CSF (Le Cesne et al, 2000;Pervaiz, 2008).…”
Section: 1775 Preoperative Radiotherapy With or Without Chemotherapymentioning
confidence: 99%
“…It is not easy to distinguish which of the side effects are related to surgery, radiotherapy or chemotherapy. Various rates of major wound complications have been reported since many factors such as; size and anatomic location of the tumor, wound closure, radiotherapy dose and volume, prior surgery, medical status and age of the patient might affect the outcome (Nielsen et al, 1991;Le Cesne et al, 2000;Kunisada et al, 2002;O'Sullivan et al, 2002;Davis et al2005;Mack et al, 2005;Kraybill et al, 2010). O'Sullivan et al reported that, acute wound complications were significantly more common with preoperative treatment compared with postoperative treatment (35 versus 17 %) (O'Sullivan et al, 2002).…”
Section: 1775 Preoperative Radiotherapy With or Without Chemotherapymentioning
confidence: 99%